New frontiers in muon-spin spectroscopy using Si-pixel detectors - Augustin, Heiko; Berger, Niklaus; Doll, Andrin; Isenring, Pascal; Köppel, Marius; Krieger, Jonas A.; Luetkens, Hubertus; Mandok, Lukas; Prokscha, Thomas; Rudzki, Thomas; Schöning, André; Salman, Zaher (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2025)
The study of novel quantum materials relies on muon-spin rotation, relaxation, or resonance (μSR) measurements. Yet, a fundamental limitation persists: many of these materials can only be synthesized in extremely small quantities, often at sub-millimeter scales. While μSR offers unique insights into electronic and magnetic properties, existing spectrometers lack a sub-millimeter spatial resolution and the possibility of triggerless pump-probe data acquisition, which would enable more advanced measurements. The General Purpose Surface-muon instrument (GPS) at the Paul Scherrer Institute (PSI) is currently limited to a muon stopping rate of 40kHz to 120kHz, a constraint that will become more pressing with the upcoming High-Intensity Muon Beam (HIMB) project. To overcome these challenges, we demonstrate the feasibility of employing ultra-thin monolithic Si-pixel detectors to reconstruct the stopping position of muons within the sample, thereby significantly enhancing the capability of measuring at higher muon rate. Additionally, we explore the first steps towards a triggerless pump-probe μSR measurement scheme. Unlike conventional pump-probe techniques that require external triggers, a triggerless readout system can continuously integrate stimuli pulses into the data stream, allowing real-time tracking of ultra-fast dynamics in quantum materials. This approach will enable the study of transient states, spin dynamics, and quantum coherence under external stimuli.